Genetic component analysis for seed yield and component traits in Indian mustard (Brassica juncea L.) (Journal of Oilseed Brassica, 2026)
Ten diverse Indian mustard genotypes/parents suitable for different sowing condition were mated in half diallele design to know the nature of gene action for inheritance of seed yield and its components traits. The results showed the presence of sufficient amount of variability among the experimental material used for the study. The estimates of σ2 S were found to be higher than the σ2 g for all characters under study that indicated preponderance of non-additive gene action for inheritance of characters thereby suggesting heterosis breeding as the best method of improvement. The genetic advance (GA) ranged from 0.043 for siliqua density on main raceme to 4.929 for plant height. Higher heritability accompanied by higher genetic advance under selection was found in case of glucosinolate content, seed yield/ plant, number of siliquae on main raceme, number of secondary branches/plant and days to maturity. For all the traits under study the value of predictability ratio was lower than unity. It represented the involvement of non-fixable type of variance. Degree of dominance ranged from 3.38 to 1.55. Therefore based on the results it can be concluded that all the characters under study were governed by non-additive gene action so heterosis breeding can be utilized for further improvement